Integration of Digital Media in Religious Activities: Potential and Challenges for Catholic Education - Toron, Vinsensius Bawa; Waton, Fidelis Regi; Dancar, Aleksander; Lelu Beding, Skolastika; Watomakin, Dominikus Boli (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This article aims to evaluate the use of digital media in the context of Catholic education, especially in religious activities. The method used in this study is content analysis as well as interviews on various aspects of the parish using ATLAS.ti7 software. It encompasses church building history, architectural design, community engagement, blessing ceremonies, photos, videos, writings, digital media integration and so forth. The results reveal that digital media has been used in a variety of church activities, including sharing photos, videos and writings and integrating digital media into religious experiences. However, its use in the context of Catholic education is still narrow. These factors include local conditions, limited resources and pastoral priorities. Nonetheless, digital media has great potential to be used as an educational tool in the Catholic context with the right approach and investment in the right resources.